Correlation between Anemia and Malaria Infection Severity in Patients with Type 2 Diabetes Mellitus in Nigeria - Adedeji David Atere; Henry Chijindu Okpoli; Kelvin Aimuemwosa Uwumarogie; Adebimpe Iyanuoluwa Moronkeji (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Malaria and diabetes mellitus are still a significant global public health problem despite the phenomenal progresses in clinical sciences related to the diseases. Both anemia and malaria parasitemia are common in developing countries. It is therefore important to diagnose and determine the correlation between anemia level and malaria infection severity in diabetic patients for better management. Methods: Patients with diabetes mellitus (DM) infected with malaria were recruited (n=50) as subjects and non-diabetic patients were used as control in this study, who were further divided into two sub-group: non-DM infected with malaria (n=25) and non-DM without malaria parasitemia (n=25). Blood sample were collected to examine the fasting blood sugar (FBS) level, packed cell volume (PCV), hemoglobin (Hb) level, and malaria parasitemia. Statistical analysis was then performed using ANOVA with a p value of less than or equal to 0.05 considered statistically significant.Results: The parasite density in DM with malaria was significantly lower (p<0.05) than in the non-DM with malaria. Interestingly, there was a higher PCV and hemoglobin level (p<0.05) in DM with malaria when compared with non-DM with malaria.Conclusion: DM patients infected with plasmodium have low parasite density but higher hemoglobin level and PCV compared to the control group. There is no correlation between the severity of anemia and malaria parasitemia in DM patients infected with malaria when compared to non-diabetic subjects infected with malaria. Further studies are needed to explore the correlation between hemoglobin level in DM and plasmodium infection